Asuhan Keperawatan pada Ny. U Dengan Gangguan Sistem Pencernaan: Abdominal Pain di Ruang Dahlia RSUD Dr. Soeselo Kabupaten Tegal - Tahta Alfina Nuranida; Tati Karyawati; Sujono Sujono (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Abdominal pain is one of the main complaints frequently encountered in patients in emergency departments and inpatient wards. This condition may be caused by various factors, ranging from gastrointestinal disorders and inflammation to reproductive system problems. Poorly managed pain can affect the patient’s quality of life, reduce daily activities, and increase anxiety. This case study aims to describe nursing care for Mrs. U, who presented with abdominal pain at dr. Soeselo Hospital, Tegal Regency. The research method applied was a case study with a nursing process approach, including assessment, diagnosis, intervention, implementation, and evaluation. The assessment revealed that the patient complained of lower abdominal pain with a pain scale of 5 (moderate), accompanied by nausea, weakness, and intermittent fever. The primary nursing diagnosis established was acute pain related to physiological injury agents. Interventions included pain management education, relaxation techniques, application of warm compresses, and collaboration in administering analgesics. The evaluation showed a decrease in pain intensity from a scale of 5 to 3, with the patient appearing calmer and showing improved sleep quality. This study emphasizes the crucial role of nurses in providing comprehensive care to reduce abdominal pain through both independent and the collaborative interventions with the medical team.